Integration of Islamic Economic Principles in Minangkabau Heritage as a Solution for Poverty Alleviation - Yuri Rahmi; Nuri Latifannisa; Zul Afdal (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study explores the integration of Islamic economic principles within the Minangkabau inheritance system as a viable solution for poverty alleviation. Focusing on the collective inheritance structure, it examines the alignment of Minangkabau matrilineal practices with Islamic values to enhance social welfare. A qualitative approach was employed, involving an in-depth analysis of inheritance customs, particularly the communal assets such as tanah ulayat (communal land) and rumah adat (traditional houses). Through interviews with local adat leaders, the study investigates how these collective assets reflect Islamic principles of justice and equity. Findings reveal that the Minangkabau inheritance system supports social welfare by preventing asset fragmentation and ensuring shared benefits within the community. This alignment between Islamic values and local customs enhances economic stability, suggesting that collective inheritance models can play a significant role in poverty alleviation efforts. Additionally, the study introduces a model that integrates cultural heritage with Islamic economic principles, underscoring its relevance for community-centered economic development. By examining the Minangkabau inheritance system through an Islamic economic lens, this study offers a unique perspective on community-driven poverty alleviation strategies.